German multicenter study analyzing antimicrobial activity of ceftazidime-avibactam of clinical meropenem-resistant pseudomonas aeruginosa isolates using a commercially available broth microdilution assay - Manzke, Jana; Stauf, Raphael; Neumann, Bernd; Molitor, Ernst; Hischebeth, Gunnar; Simon, Michaela; Jantsch, Jonathan; Rödel, Jürgen; Becker, Sören Leif; Halfmann, Alexander; Wichelhaus, Thomas A.; Hogardt, Michael; et al. (Antibiotics, 2022)
Multidrug resistance is an emerging healthcare issue, especially concerning Pseudomonas aeruginosa. In this multicenter study, P. aeruginosa isolates with resistance against meropenem detected by routine methods were collected and tested for carbapenemase production and susceptibility against ceftazidime-avibactam. Meropenem-resistant isolates of P. aeruginosa from various clinical materials were collected at 11 tertiary care hospitals in Germany from 2017-2019. Minimum inhibitory concentrations (MICs) were determined via microdilution plates (MICRONAUT-S) of ceftazidime-avibactam and meropenem at each center. Detection of the presence of carbapenemases was performed by PCR or immunochromatography. For meropenem-resistant isolates (n = 448), the MIC range of ceftazidime-avibactam was 0.25-128 mg/L, MIC90 was 128 mg/L and MIC50 was 16 mg/L. According to EUCAST clinical breakpoints, 213 of all meropenem-resistant P. aeruginosa isolates were categorized as susceptible (47.5%) to ceftazidime-avibactam. Metallo-β-lactamases (MBL) could be detected in 122 isolates (27.3%). The MIC range of ceftazidime-avibactam in MBL-positive isolates was 4-128 mg/L, MIC90 was >128 mg/L and MIC50 was 32 mg/L. There was strong variation in the prevalence of MBL-positive isolates among centers. Our in vitro results support ceftazidime-avibactam as a treatment option against infections caused by meropenem-resistant, MBL-negative P. aeruginosa.
This article belongs to the special issue "Carbapenem-Resistant Organisms (CRO) as leading cause of hospital associated infections"
Gesehen am 27.07.2022